Putting The Community Back Into Inquiry Based Learning. Why Inquiry Based Learning Should Look Back As Well As Forward. - Ra Davis (New Zealand Journal of Teachers' Work)
The current quest to implement inquiry based learning would be all the better for some philosophical enrichment. The emphasis of successful enquiry lies in developing the classroom environment into a true community of inquiry. This community has its roots firmly planted in the traditions of philosophy.